ChemInform Abstract: Darwinolide, a New Diterpene Scaffold That Inhibits Methicillin‐Resistant Staphylococcus aureus Biofilm from the Antarctic Sponge Dendrilla membranosa. Issue 44 (13th October 2016) - von Salm, Jacqueline L.; Witowski, Christopher G.; Fleeman, Renee M.; McClintock, James B.; Amsler, Charles D.; Shaw, Lindsey N.; Baker, Bill J.
Abstract: Darwinolide (I) shows cytotoxic activity.